Rollator use does not consistently change the metabolic cost of walking in people with Chronic Obstructive Pulmonary Disease - Hill, Kylie; Dolmage, T.; Woon, L.; Brooks, D.; Goldstein, R. (Elsevier, 2012)
Objectives: To (1) evaluate whether the use of a rollator changed metabolic cost during a controlled walking task, and (2) explore relationships between the difference in dyspnea and metabolic cost associated with rollator use. Design: Single-group interventional study in which patients completed 2 corridor walks: 1 without and 1 with a rollator, at the same individualized constant speed. Setting: Rehabilitation hospital. Participants: Patients with chronic obstructive pulmonary disease (N=15; 10 men; median age [interquartile range; IQR]=69 [12]y; forced expiratory volume in 1 second=42 [20]% predicted). Intervention: Rollator use. Main Outcome Measures: Oxygen uptake, converted to metabolic equivalent units (METs), and minute ventilation were measured throughout both tasks using a portable gas analysis system; dyspnea and arterial oxygen saturation (SpO2) were collected on completion. Results: Median [IQR] walk speed [IQR] was 48 (10)m/min. Walking with a rollator, compared with walking without, reduced dyspnea (median [IQR]=1.0 [1.5] vs 2.0 [2.0]; P=.01) without changing energy expenditure (median [IQR]=2.8 [1.2] vs 3.2 [0.9] METs; P=.65), minute ventilation (median [IQR]=30.3 [9.6] vs 27.7 [9.9]L/min; P=.50), or SpO2 (median [IQR]=92 [8]% vs 94 [10]%; P=.41). The association between the reduction in dyspnea and any difference in energy expenditure related to rollator use was of borderline significance (rs=.50; P=.06). Six of the 8 participants who experienced a reduction in dyspnea also demonstrated a reduction in the metabolic cost of walking. Conclusions: The mechanism responsible for the amelioration in dyspnea during rollator-assisted walking is multifactorial. A reduction in the metabolic cost of walking may play a part in some, but not all, patients.